ABOUT THEORETICAL ASPECTS OF THE DEVELOPMENT OF COMMUNICATION SKILLS - BRAICOV, Andrei; POPOVICI, Ilona (Acta et Commentationes, Sciences of Education, 2020)
The present article briefly describes the researches carried out in order to elucidate the theoretical foundations and the particularities of the process of developing the communication competence, the determination and justification of the environments favorable to the development of this competence, the establishment of the principles that must be respected and realized for its effective formation and development, as well as factors that significantly influence the process of developing communication competence.